Implementasi Tanda Tangan Digital Pada Aplikasi Rekam Medis Elektronik - Dwi Satria Putra; Ahmad Syazili; Syahril Rizal R I; Nia Oktaviani (STMIK Budi Darma, 2023)
This study aims to implement digital signatures in the electronic medical record application at Klinik Rosha. The Agile methodology is employed, consisting of stages such as planning, implementation, software testing, documentation, deployment, and maintenance. It is expected that the implementation of digital signatures in the electronic medical record application at Klinik Rosha will improve the efficiency and accuracy of the process of recording and verifying medical data. Additionally, the use of digital signatures is anticipated to enhance the security of medical data and reduce the risk of data forgery. This research has a positive contribution to the development of electronic medical record applications in Indonesia and facilitates access to medical information for patients and healthcare professionals. This step represents a promising breakthrough in improving and strengthening the working system at Klinik Rosha. By implementing digital signatures, the process of recording and verifying medical data will become more efficient and accurate, providing significant benefits to the clinic's operations. The use of digital signatures will also increase the security of medical data, reduce the risk of data forgery, and provide better protection for sensitive medical information. With digital signatures, the integrity and authenticity of medical data can be better maintained, ensuring the confidentiality and authenticity of sensitive information. This research is a significant step forward in the development of electronic medical record applications, with a positive impact on Klinik Rosha